Substâncias poliméricas extracelulares (EPS) e quorum sensing de biofilmes mono e multiespécies - Aquino, Nathanyelle Soraya Martins de (2017)
The poultry industry is one of the most important sectors of the Brazilian economy, and microbiological control should be a priority to maintain product quality. One of the barriers observed is the contamination of food by contact with surfaces adhered by microorganisms. This adhesion, called biofilm, gives the bacterial community greater protection and resistance against the action of sanitizers, making hygiene difficult. During the process of biofilm formation the bacteria release autoinductive molecules responsible for cellular communication that act by activating virulence genes, encouraging the formation of biofilms, stimulating the production of extracellular polymer substances (EPS), among other functions. The objective of this work was to evaluate the formation of monospecies and multispecies bi ofilms by pathogens previously isolated from the avian processing environment: S. Enteritidis, E. coli, C. jejuni and L. monocytogenes. Also, the quantification of extracellular polymer substances (EPS), the presence of quorum sensing molecules and the effects of hygienization treatments on EPS of these biofilms. The temperatures and surfaces used for biofilm formation were chosen to mimic the processing environment of the poultry industry. The results showed that all the microorganisms were able to adhere to the analyzed surfaces, except for C. jejuni, whose quantification was not possible under any of the conditions tested. Bacteria showed higher capacity for monospecific biofilm formation, with similar adhesion capacity on all surfaces. There was a decrease in the quantification when in multispecies interactions, and the polymers provided greater adhesion than the stainless steel. There was ability to form biofilms even at refrigeration temperatures, with S. Enteritidis being the strain most adapted to the conditions tested. In agreement with the results above, it was observed that the quantification of EPS was higher in temperatures critical for the growth of microorganisms, probably because it is used as a survival tool, acting as a barrier against thermal stress. Although EPS impedes the penetration of sanitizers into the bacterial community, it can be seen that water at 85ºC and 2% sodium hypochlorite were effective in breaking the matrix, with less EPS in the samples after the use of water heated to 85°C. Regarding the study of quorum sensing in biofilms, it was not possible to detect the presence of auto-inducers in any of the interactions studied. The data obtained reinforce the importance of the study of biofilms as an aid to the industry, highlightin g the crucial points that must be worked in order to avoid contamination of food. The modification of surfaces may be a strategy to inhibit microbial adhesion, since the evaluated polyethylene, polyurethane and stainless steel, obtained directly from poult ry slaughterhouse, allowed high quantification. The maintenance of the foods in the cold chain can be used to delay the adhesion of the microorganisms, because, although there was biofilm formation in the cooling temperatures, it was smaller when compared to higher temperatures. Therefore, modified surfaces, hygienizations at appropriate times, combined with refrigeration temperatures, can be an effective alternative in the control of biofilms in the food industry.